Eradication of Biofilm-Like Microcolony Structures of Borrelia burgdorferi by Daunomycin and Daptomycin but not Mitomycin C in Combination with Doxycycline and Cefuroxime - Feng, Jie; Weitner, Megan; Shi, Wanliang; Zhang, Shuo; Zhang, Ying (Frontiers in Microbiology, 2016)
Lyme disease, caused by Borrelia burgdorferi, is the most common vector-borne disease in the United States and Europe. While the majority of Lyme disease patients can resolve their symptoms if treated promptly, 10–20% of patients suffer from prolonged symptoms called post-treatment Lyme disease syndrome (PTLDS). Although the cause for PTLDS is unclear, one possibility is the presence of bacterial persisters not effectively cleared by the current Lyme antibiotics. Recent studies identified several drug candidates including daptomycin, daunomycin, doxorubicin, and mitomycin C that had good activity against B. burgdorferi persisters. However, their relative activities against B. burgdorferi persisters have not been evaluated under the same conditions. In this study, we tested the anti-persister activities of these drugs against both 7-day and 15-day old stationary phase cultures of B. burgdorferi individually as well as in combination with Lyme antibiotics doxycycline and cefuroxime (Ceftin). Our findings demonstrate daunomycin and daptomycin were more active than mitomycin C in single drug comparison at 10 and 20 μM, as well as in drug combinations with doxycycline and cefuroxime. In addition, daunomycin was more active than doxorubicin which correlated with their ability to stain and accumulate in B. burgdorferi. The two drug combination of doxycycline and cefuroxime was unable to eradicate biofilm-like microcolonies of B. burgdorferi persisters. However, the addition of either daunomycin or daptomycin to the doxycycline + cefuroxime combination completely eradicated the biofilm-like structures and produced no visible bacterial regrowth after 7 and 21 days, while the addition of doxorubicin was unable to prevent regrowth at either 7 or 21 day subculture. Mitomycin C in combination with doxycycline and cefuroxime caused no regrowth at 7 days but visible spirochetal regrowth occurred after 21 day subculture. Furthermore, we found that cefuroxime (Ceftin), the third commonly used and most active antibiotic to treat Lyme disease, could replace cefoperazone (a drug no longer available in the US) in the daptomycin + doxycycline combination with complete eradication of the biofilm-like structures as shown by lack of any regrowth in subcultures. Our findings may have implications for improved treatment of Lyme disease.